Pantheologies : gods, worlds, monsters - Rubenstein, Mary-Jane (Columbia University Press, 2018)
Mary-Jane Rubenstein provides a conceptual genealogy of pantheisms. What makes pantheism "monstrous"--At once repellent and seductive-is that it scrambles the raced and gendered distinctions that Western philosophy and theology insist on drawing between activity and passivity, spirit and matter, animacy and inanimacy, and creator and created. -- Provided by publisher